Kewenangan Notaris Melakukan Pekerjaan di Luar Wilayah Jabatan - Dhiya, Siti Raskha Ghina Farraz (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this research is to examine and analyze the authority of Notaries to carry out ork outside the region, including elements of unfair business competition for Notaries. and to review and analyze the authority of the Notary Supervisory Board regarding violations of unfair business competition for Notaries. Meanwhile, the research method used is Normative legal research, namely a method that uses primary legal material sources in the form of statutory regulations, legal theories and expert opinions, to analyze and draw conclusions about the problems used to test and study legal materials, hile the research results are obtained It is known that this unhealthy competition itself is related to Notaries ho carry out positions outside their area of office, such as ratifying deeds of establishment of business entities and legal entities, ratifying an agreement, stipulating an agreement. So the correlation is ith unhealthy business competition according to the provisions of Law Number 5 of 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition, namely Article 17, and related to the authority of the Notary Supervisory Council hich carries out supervision, inspection and imposes sanctions on Notaries, and at every level The Notary Supervisory Council consists of the Regional Supervisory Council (MPD), Regional Supervisory Council (MPW); and the Central Supervisory Council (MPP), so that for violations of unfair business competition, efforts to enforce the Notary's code of ethics, namely based on Article 85 of Law Number 30 of 2004 concerning the Position of Notaries by placing a verbal arning in the first order of giving sanctions, is a arning to notary from the Supervisory Council hich if not fulfilled is followed up ith ritten sanctions. If this sanction is not complied ith by the notary concerned, subsequent sanctions can be imposed in stages.